The meaning of family medicinal plants for family health: A phenomenological study among rural housewives - Annisa, Tia Nur; Muis, Noor (Science Center Group, 2025)
Background: Medicinal plants have long played an essential role in primary health care, especially in rural areas where access to biomedical services is limited. In many families, their use is deeply rooted in cultural traditions and intergenerational practices. Understanding how rural housewives perceive and experience medicinal plant use is vital to preserving ethnomedicinal knowledge and strengthening culturally grounded health strategies. This study aimed to explore the meaning of family medicinal plants for family health from the lived experiences of rural housewives. Methods: A qualitative study using a phenomenological approach was conducted with 12 rural housewives who were primary caregivers in their households and had regular experience using medicinal plants. Participants were recruited through purposive sampling and interviewed using in-depth semi-structured interviews. Data were analyzed using Colaizzi’s seven-step method to identify significant statements, formulate meanings, cluster themes, and construct the essential structure of the phenomenon. Results: Four major themes emerged: (1) medicinal plants as a family health heritage—participants described intergenerational transmission of knowledge as a symbol of family care; (2) empowerment and self-reliance in health care—participants expressed confidence and autonomy in treating common illnesses while reducing economic burden; (3) cultural and spiritual meaning of plant use—participants viewed plants as sacred gifts, integrating prayers and rituals into their preparation; and (4) challenges and adaptations in preserving knowledge—participants highlighted the decline of interest among younger generations while adapting by blending traditional and modern remedies. Conclusion: Family medicinal plants hold profound cultural, emotional, and practical significance in maintaining family health among rural housewives. They embody cultural heritage, empowerment, spirituality, and resilience, yet face threats of knowledge erosion.